To rewrite the equation \(4x^3 - 12 + 3 = 10\) in two equations joined by “and,” we first simplify the equation.

Starting with the original equation:
\[
4x^3 - 12 + 3 = 10
\]
we can simplify it to:
\[
4x^3 - 9 = 10
\]
Next, we move \(10\) to the left side:
\[
4x^3 - 9 - 10 = 0
\]
which simplifies to:
\[
4x^3 - 19 = 0
\]

Now, we can express this as two separate equations. For example, we can set \(4x^3 = 19\) and recognize that \(y=10\) from the original equation context:

So, the rewritten form is:
\[
4x^3 = 19 \quad \text{and} \quad y = 10
\]
where \(y\) represents the constant derived from the original equation.make this smaller

1 answer

To rewrite the equation \(4x^3 - 12 + 3 = 10\) in two equations joined by "and," we first simplify it:

Starting with: \[ 4x^3 - 12 + 3 = 10 \] we simplify it to: \[ 4x^3 - 9 = 10 \] Next, move \(10\) to the left side: \[ 4x^3 - 19 = 0 \]

We can express this as: \[ 4x^3 = 19 \quad \text{and} \quad y = 10 \]

Thus, the final form is: \[ 4x^3 = 19 \quad \text{and} \quad y = 10 \]

Similar Questions
    1. answers icon 1 answer
  1. VARIABLE EQUATIONS & INEQUALITIES UNIT TEST:REWRITE THE EQUATION _4X____ + 3 = 10 IN TWO EQUATIONS JOINED BY "AND." 3X- 12
    1. answers icon 1 answer
  2. VARIABLE EQUATIONS & INEQUALITIES UNIT TEST:REWRITE THE EQUATION \frac{4x}{3x-12}+3=10 IN TWO EQUATIONS JOINED BY "AND."
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions